Intermetallic phases meet intermetalloid clusters. (11th June 2021) - Schütz, Max; Gemel, Christian; Klein, Wilhelm; Fischer, Roland A.; Fässler, Thomas F.
Abstract : In this article intermetalloid clusters of Cu–Zn, Cu–AI, Cu–Sn, and Cu–Pb are discussed. Abstract : In this article intermetalloid clusters of Cu–Zn, Cu–AI, Cu–Sn, and Cu–Pb are discussed. Intermetallic compounds based on these metal combinations are of the Hume-Rothery type with well-defined structures related to the valence electron count of the involved metals. Many Zintl-type and molecular clusters with these metals are known with remarkable structural parallels to the respective solid-state phases. On several examples, this article discusses intermetalloid clusters in terms of their metal core structures and relates them to structural principles in intermetallic solid-state phases. Also the syntheses of such clusters are addressed. Zintl-type and molecular clusters are most generally accessible from organometallic precursor complexes with redox processes between the different metals as an underlying synthesis concept.